‘Dual Sensory Loss Protocol’ for Communication and Wellbeing of Older Adults With Vision and Hearing Impairment – A Randomized Controlled Trial - Vreeken, Hilde L.; van Nispen, Ruth M. A.; Kramer, Sophia E.; van Rens, Ger H. M. B. (Frontiers in Psychology, 2020)
Objectives: Many older adults with visual impairment also have significant hearing loss. The aim was to investigate the effectiveness of a newly developed Dual Sensory Loss (DSL) protocol on communication and wellbeing of older persons with DSL and their communication partners (e.g. spouse or child) in the Netherlands and Belgium. Methods: Participants (N=131) and their communication partners (n=113) were randomized in the “DSL-protocol” intervention group or waiting-list control group. The intervention took 3 to 5 weeks. Occupational therapists focused on optimal use of hearing aids, home-environment modifications and effective communication strategies. The primary outcome was the Communication Strategies domain of the Communication Profile for the Hearing Impaired (CPHI). Secondary outcomes measured in participants were the Low Vision Quality Of Life Adjustment subscale, the Center for Epidemiological Studies - Depression scale, De Jong Gierveld Loneliness Scale and the Fatigue Assessment Scale. The Hearing Handicap and Disability Inventory (HHDI) - Reaction Of Others subscale and the Care-related Quality Of Life – 7 Dimensions was measured in communication partners. Measurements were taken at baseline and 3-month follow-up. Linear mixed models (LMM) were used to analyze effects between groups over time for every outcome measure. Results: Intention-to-treat analyses showed a significant effect of the DSL-protocol on the use of verbal strategies (effect size SMD=0.60, 95%CI: 0.25 to 0.95) in favor of the control group, however, this effect was non-significant after adjustment for confounding. Effect sizes of other outcomes varied between -0.23 [-0.57, 0.12] and 0.30 [-0.05, 0.64]. The LMM showed a significant effect on the HHDI-Reaction of others scale in favor of communication partners in the treatment group, however, the effect size was very small and non-significant 0.12, 95%CI [-0.27 to 0.51]. Adjusted analyses did not reveal treatment effects. Conclusions: The DSL-protocol did not clearly contribute to the enhancement of communication and wellbeing in DSL-patients. Possible reasons for the lack of effects are OTs not being comfortable giving advice on communication and psychosocial issues or the short-term treatment and follow-up period. Further study is warranted to find out how the protocol may be adapted or whether it is necessary to involve mental healthcare professionals.